High-frequency ultrasound in the diagnosis and treatment of skin neoplasms - Płocka, Maria; Czajkowski, Rafał (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2023)
High-frequency ultrasonography (HFUS) is a non-invasive and highly repetitive medical imaging method with a great and still rising value in the diagnostic process of skin tumours. It accompanies the physician’s examination, dermoscopy, and biopsy; facilitates real-time assessment of locoregional staging and planning of surgical excision; and provides postoperative inspection of treatment results. The aim of this review article is to discuss HFUS application in common cutaneous malignant tumours while depicting the use of both the grayscale and colour Doppler methods.